2017
DOI: 10.18632/oncotarget.23225
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α activates transforming growth factor-β1/Smad signaling and increases collagen deposition in dermal fibroblasts

Abstract: Hypoxia of local tissue occurs during the scar formation; however, the degree of ischemia and hypoxia in the central areas of keloids is more serious than those in normal scars. Hypoxia-induced factor (HIF), is one of the main cellular responses to hypoxia, allowing cells to adapt to low-oxygen conditions. We investigated the correlation among hypoxia, transforming growth factor-β1/Smad signaling and collagen deposition. Hypoxia up-regulated TGF-β1, Smad2/3, p-Smad2/3, Smad4, and total collagen in both normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 44 publications
5
77
0
Order By: Relevance
“…PFN2 is an epigenetic regulator of SMAD2/3 (Mothers against decapentaplegic homolog 2/3) [53], which in turn has been shown to promote metastasis in cancer cells [54]. SMAD2 and SMAD3 are also regulated by HIF-1α [55]. In the knowledge-based STRING network, SMAD3 is directly linked to HIF-1α.…”
Section: Protein Association Network Identify Signaling Components Pmentioning
confidence: 99%
“…PFN2 is an epigenetic regulator of SMAD2/3 (Mothers against decapentaplegic homolog 2/3) [53], which in turn has been shown to promote metastasis in cancer cells [54]. SMAD2 and SMAD3 are also regulated by HIF-1α [55]. In the knowledge-based STRING network, SMAD3 is directly linked to HIF-1α.…”
Section: Protein Association Network Identify Signaling Components Pmentioning
confidence: 99%
“…Unlike previous techniques, the 'scar-in-a-jar' assay enables the visualisation and quantification of rapid deposition and cross-linking of mature collagen fibrils, more closely resembling the disorganized fibres characteristic of IPF lesions [11,13,30]. In contrast, previous assays have focused on quantifying soluble collagens using the Sircol assay [31] or measuring soluble P1NP (procollagen type I N-terminal propeptide [32]), both of which reflect surrogate markers of ECM turnover [33]. Other methods of quantifying ECM deposition include the histological Picro-Sirius red staining, however this lacks resolution and collagen specificity [34].…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 has been shown to play a role in T cell differentiation [39], and especially in regulation of Tregs [39]. It was clearly shown that hypoxic conditions via HIF-1a induces transforming growth factor-beta (TGF-β) [40][41][42] which is the main transcription factor involved in the regulation of Th17 and Treg balance. In the absence of proinflammatory cytokines, TGF-β drives differentiation into Treg cells [43][44][45].…”
Section: Discussionmentioning
confidence: 99%